Extract Of Nuts As A Natural-Nitrogen Source In The Making Of Cane Nata - Febriani, Anggun Safitri; Paramita, Octavianti (Universitas Negeri Semarang, 2020)
Natural nitrogen sources derived from the extracts of green beans, soybeans, and peanuts used for making sugarcane juice have been studied. Organoleptic quality for nata was analyzed by indicators of color, texture, aroma, and taste. The level of community preference for sugarcane juice on sugarcane juice is observed in the community. The data analysis method used single classification Variance Analysis for selection using descriptive analysis, fiber content using proximate analysis, and protein content using the Kjeldahl method. The single classification variant analysis results show significant differences in the aspects of color and texture. The results of the community preference test were selected nata using ZA protein. The amounts of fiber and protein in the sugarcane juice and green bean extract samples were 0.79% and 24.319%, respectively, as best results. Other sugarcane juice's fiber and protein content is lowest than 0.68% and 5.359%, respectively. The best quality organoleptic qualities were samples with fertilization using ZA and green beans. The observation results showed that the sugar cane juice with green bean extract was more acceptable to the community and had better nutritional content.